Mapping public urban green spaces based on OpenStreetMap and Sentinel-2 imagery using belief functions: data and source code - Ludwig, Christina; Hecht, Robert; Lautenbach, Sven; Schorcht, Martin; Zipf, Alexander (Universität, 2020)
Public urban green spaces are important for the urban quality of life. Still, comprehensive open data sets on urban green spaces are not available ...